Success and Impact in Widening Participation Policy: What Works and How Do We Know? - Harrison, N; Waller, R (Palgrave Macmillan, 2017)
Efforts to widen the participation in higher education for disadvantaged and under-represented groups are common to many countries. In England, higher education institutions are required by government to invest in ‘outreach’ activities designed to encourage such groups. There is increasing policy and research interest around the effectiveness of these activities and how this might be evaluated. This paper reports the results of a project designed to explore concepts of ‘success’ and ‘impact’ with two generations of practitioner-managers working in this field, including extended telephone interviews with ten active in the mid-2000s, and online questionnaires from 57 engaged in the mid-2010s. The paper concludes that the drive to ‘measure the measurable’ may be undermining successful activities, while unhelpful inter-institution competition has replaced the co-operative ethos and wider social justice aims that dominated ten years ago.